Parenting for primates - Smith, Harriet J. (Harvard University Press, 2005)
Parenting for Primates is a delightful combination of hard facts and good stories about us and our close relatives. Harriet Smith shows us superdads, devoted and abusive parents, and blended families among nonhuman and human primates too. An important and timely book.